Petrophysics study of sand stone core to the accuracy of ultrasonic pulse velocity - Samsuri, Ariffin; Herianto, Herianto; Setyowiyoto, Jarot (2012)
Several cores sand stones Malaysian from out croup to determin their petrophysical properties in laboratories. Reservoir rocks are mostly consisting of sedimentary rock. There are few important characteristics of reservoir rocks in petroleum industry that need to be studied for further development. Among them are petrophysical properties such as density, porosity, water saturation and permeability. In this study tests have been carried out to examine the relationship between petrophysical properties and acoustic velocity using Ultrasonic Pulse Velocity Method (UPVM). Result of the laboratory test have been used to determin physical rock properties from acoustic velocity data.